2017
DOI: 10.26633/rpsp.2019.99
|View full text |Cite
|
Sign up to set email alerts
|

Archival data review of intimate partner homicide-suicide in Jamaica, 2007 – 2017: focus on mental health and community response

Abstract: Objective. To identify social and behavioral patterns and mental health concerns associated with intimate partner homicide-suicide (IPHS) in Jamaica through an analysis of media and police reports. Methods. This was an archival data review of police records and print, radio, and television reports of IPHS incidents from January 2007-June 2017 in Jamaica. The 27 cases found were qualitatively analyzed using pre-identified codes and open coding to generate themes and patterns. Results. A prevalence rate of 0.1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The low referral rate may be linked to poor mental health literacy and urgency for professional care particularly for adults, along with existing mental health stigma and limited availability of public mental health facilities that are common in low- and middle-income countries (LMICs) (Asher et al, 2017). Our results support the need to sensitise community leaders to better encourage mental health-seeking behaviours (Bernard et al, 2018; Pottinger et al, 2019) and promote mental health education.…”
Section: Discussionsupporting
confidence: 72%
“…The low referral rate may be linked to poor mental health literacy and urgency for professional care particularly for adults, along with existing mental health stigma and limited availability of public mental health facilities that are common in low- and middle-income countries (LMICs) (Asher et al, 2017). Our results support the need to sensitise community leaders to better encourage mental health-seeking behaviours (Bernard et al, 2018; Pottinger et al, 2019) and promote mental health education.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies on IPFS perpetrators’ risk factors showed that it is almost always characterized by an intimate male perpetrator and a female victim [ 3 , 4 , 5 , 6 , 9 , 10 , 15 , 30 , 33 , 34 , 35 , 36 , 37 ]. Perpetrators are, in most cases, of a white racial background [ 9 , 30 ] with a medium or low socioeconomic background [ 4 , 10 ], and older than the victim [ 4 , 5 , 12 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on IPFS perpetrators’ risk factors showed that it is almost always characterized by an intimate male perpetrator and a female victim [ 3 , 4 , 5 , 6 , 9 , 10 , 15 , 30 , 33 , 34 , 35 , 36 , 37 ]. Perpetrators are, in most cases, of a white racial background [ 9 , 30 ] with a medium or low socioeconomic background [ 4 , 10 ], and older than the victim [ 4 , 5 , 12 , 37 ]. They generally used a gun for committing IPFS [ 3 , 4 , 5 , 6 , 9 , 10 , 11 , 35 , 38 , 39 , 40 ] and most often in a relationship with the current or ex-intimate partner (e.g., married, cohabiting, recently separated) [ 3 , 4 , 5 , 6 , 9 , 10 , 12 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations